Analisis Pelaksanaan Kebutuhan Diklat Bagi Tenaga Kependidikan di Fakultas Pendidikan Olahraga dan Kesehatan (FPOK) Universitas Pendidikan Indonesia - Indra Muliawan; Sedarmayanti Sedarmayanti; Nefi Aris Ambar Asmara (Jurnal Media Administrasi Terapan, 2023)
This study aims to analyze the need for training and education for education personnel at the Faculty of Sports and Health Education (FPOK) Universitas Pendidikan Indonesia. The research used in this study is a descriptive method with a qualitative approach. The process of collecting data from this research was obtained through interviews and documentation studies. Researchers used triangulation of data/data sources. The results of the study are known by analysis of training needs found several findings including there was still a competency gap between employees, namely a lack of understanding of work assignments and problem-solving in work assignments, although in the process employees asked each other to work with colleagues when there were obstacles.